2020
DOI: 10.1128/jvi.01093-19
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Rhesus Monkey Rhadinovirus Deleted of Glycoprotein L Establishes Persistent Infection of Rhesus Macaques and Elicits Conventional T Cell Responses

Abstract: A replication-competent, recombinant strain of rhesus monkey rhadinovirus (RRV) expressing the Gag protein of SIVmac239 was constructed in the context of a glycoprotein L (gL) deletion mutation. Deletion of gL detargets the virus from Eph family receptors. The ability of this gL-minus Gag recombinant RRV to infect, persist, and elicit immune responses was evaluated after intravenous inoculation of two Mamu-A*01+ RRV-naive rhesus monkeys. Both monkeys responded with an anti-RRV antibody response, and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…To ultimately address the correlation between receptor- and tissue-tropism, in vivo studies using receptor-de-targeted mutants to analyze cell and tissue tropisms will be required. The importance of in vivo studies is also supported by a recent report that showed that a gL-null RRV mutant still established persistent infection in the B cell compartment upon intravenous inoculation, while infection of B cells in vitro was drastically reduced [ 24 ], a finding that could be explained by the gL-independent usage of Plxdc1/2 for B cell infection in vivo . At a minimum, our data on RRV-YFP ΔgL infection of Plxdc1 and Plxdc2 overexpressing Raji cells ( Fig 6B ) confirms that RRV can efficiently use Plxdc1 and Plxdc2 as entry receptors in the absence of gL.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…To ultimately address the correlation between receptor- and tissue-tropism, in vivo studies using receptor-de-targeted mutants to analyze cell and tissue tropisms will be required. The importance of in vivo studies is also supported by a recent report that showed that a gL-null RRV mutant still established persistent infection in the B cell compartment upon intravenous inoculation, while infection of B cells in vitro was drastically reduced [ 24 ], a finding that could be explained by the gL-independent usage of Plxdc1/2 for B cell infection in vivo . At a minimum, our data on RRV-YFP ΔgL infection of Plxdc1 and Plxdc2 overexpressing Raji cells ( Fig 6B ) confirms that RRV can efficiently use Plxdc1 and Plxdc2 as entry receptors in the absence of gL.…”
Section: Discussionmentioning
confidence: 85%
“…While for KSHV, in addition to Eph family receptors, several membrane proteins have been proposed as cellular receptors for different viral glycoproteins mediating either attachment or entry on a range of target cells (reviewed in [ 21 ]) the receptor usage of RRV is comparatively less well characterized. Nevertheless, studies using receptor knock-down or knockout [ 14 , 22 ], receptor- and ligand-mediated blocking [ 15 , 23 ], and Eph de-targeted virus mutants [ 23 , 24 ] showed that both viruses and in particular RRV can infect various cells partially or completely independently of the Eph-interaction, which suggests that RRV engages at least one additional entry receptor that can functionally substitute for the Eph-interaction. This notion is also supported by a recent in vivo study that demonstrated that an RRV mutant deleted of gL and therefore unable to interact with Eph receptors still establishes persistent infection in RRV-naïve rhesus macaques upon intravenous inoculation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To ultimately address the correlation between receptor-and tissuetropism, in vivo studies using receptor-de-targeted mutants to analyze cell and tissue tropisms will be required. The importance of in vivo studies is also supported by a recent report that showed that a gLnull RRV mutant still established persistent infection in the B cell compartment upon intravenous inoculation, while infection of B cells in vitro was drastically reduced (24), a finding that could be explained by the gL-independent usage of Plxdc1/2 for B cell infection in vivo. At a minimum, our data on RRV-YFP ΔgL infection of Plxdc1 and Plxdc2 overexpressing Raji cells (Fig 6) confirms that RRV can efficiently use Plxdc1 and Plxdc2 as entry receptors in the absence of gL.…”
Section: Ebv and Hcmv A Clear Correlation Between Receptor Usage Dementioning
confidence: 78%
“…While for KSHV, in addition to Eph family receptors, several membrane proteins have been proposed as cellular receptors for different viral glycoproteins mediating either attachment or entry on a range of target cells (reviewed in (21)) the receptor usage of RRV is comparatively less well characterized. Nevertheless, studies using receptor knock-down or knockout (14,22), receptor-and ligand-mediated blocking (15,23), and Eph de-targeted virus mutants (23,24) showed that both viruses and in particular RRV can infect various cells partially or completely independently of the Eph-4 interaction, which suggests that RRV engages at least one additional entry receptor that can functionally substitute for the Eph-interaction. This notion is also supported by a recent in vivo study that demonstrated that an RRV mutant deleted of gL and therefore unable to interact with Eph receptors still establishes persistent infection in RRV-naïve rhesus macaques upon intravenous inoculation (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation